Analisis Kelayakan Investasi Mesin Pemotong Kerupuk Ikan di UMKM Dua Putri Sangkapura Bawean - Reza Fahrezi, Moh.; Lokajaya, I Nyoman (Fakultas Teknik Universitas Tulang Bawang, 2024)
UMKM Dua Putri is a home-based business that produces typical Bawean fish crackers located in Gresik district which has 4 products, namely: Large Roasted Crackers, Small Roasted Crackers, Original Leko Crackers, Leko Balado Crackers. The problem is that when carrying out the process of cutting cracker cakes, we still use manual cutting. Even though there is a dough rolling machine and a cracker roasting machine, it is still overwhelming during the cutting process. Therefore, the researcher's aim is to analyze the feasibility of investing in a cutting machine as a consideration so that time is not wasted and is efficient based on the machine's age of 7 years. The results of calculations using the NPV method yield a result of Rp. 58,025,817 (NPV>0), IRR of 19.02% (IRR>10% initial interest rate), BCR of (BCR>1), and proven investment returns from BEP results with data interpolation for 2 years and 7 months. Based on calculations, this investment is feasible or can be done. Keywords: BCR, BEP, Cutting, IRR, Investment Feasibility, NPV,